2018
DOI: 10.1021/acs.iecr.8b00682
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth/Transition Metal Oxides for Syngas Tar Reforming: A Model Compound Study

Abstract: A major problem in biomass or coal gasification is removal of syngas byproducts such as H2S, NH3, and tars (heavy hydrocarbons) that cause catalyst deactivation and clogging problems downstream. Rare earth oxides (REOs) doped with transition metals (TMs) are promising catalysts for tar reforming. With propane as a model compound, we compared such catalysts to a typical supported Ni catalyst, and also to recent density functional theory (DFT) results modeling these systems. The REO/TM catalysts are active over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Sulphur poisoning is resistible with the addition of certain components; CeO 2 has been found to help prevent sulphur poisoning through the exploitation of the oxygen mobility that this material is known for. The mobile oxygen is then able to interact with the S present on the catalyst sites to form sulphur oxides that are more easily removed at the high temperatures used for reforming reactions [40][41][42]. Another method to prevent S poisoning is using alkaline materials as sacrificial components to adsorb the S before it can reach the catalyst active sites [39,43].…”
Section: Poisoningmentioning
confidence: 99%
“…Sulphur poisoning is resistible with the addition of certain components; CeO 2 has been found to help prevent sulphur poisoning through the exploitation of the oxygen mobility that this material is known for. The mobile oxygen is then able to interact with the S present on the catalyst sites to form sulphur oxides that are more easily removed at the high temperatures used for reforming reactions [40][41][42]. Another method to prevent S poisoning is using alkaline materials as sacrificial components to adsorb the S before it can reach the catalyst active sites [39,43].…”
Section: Poisoningmentioning
confidence: 99%
“…This behavior was explained by authors as a result of high copper dispersion in the compound oxides, which facilitated the reduction of iron oxides to metallic iron and prevented catalytic deactivation due to a decrease in the surface area of the catalysts during the reaction. The steam reforming of naphthalene with syngas mixtures and H 2 S over rare earth oxides (REOs) mixed with transition metals was reported by Li et al It was found that Fe- and Mn-doped supported REOs are promising tar removal catalysts with higher sulfur tolerance, less coking, and less methanation than conventional Ni-based high-temperature reforming catalysts in the temperature range of 650–800 °C. This phenomenon was related to the increased generation of oxygen vacancies in the metal-doped REOs.…”
Section: Catalysts For Biomass Tar Crackingmentioning
confidence: 99%
“…& Engineering Chemistry Research of naphthalene with syngas mixtures and H 2 S over rare earth oxides mixed with transition metals was reported by Li et al98 It was found that Fe-and Mn-doped supported REOs are promising tar removal catalysts with higher sulfur tolerance, less coking, and less methanation than conventional Ni-based high-temperature reforming catalysts in the temperature range of 650−800 °C. This phenomenon was related to the increased generation of oxygen vacancies in the metal-doped REOs.…”
mentioning
confidence: 98%
“…[1,10] Doping transition metals into CeO 2 is a promising way to create oxygen vacancy and lattice distortion, thus leading to enhanced catalytic performance. [11][12][13][14][15][16][17][18] Among various doped CeO 2 catalysts, Ce 1-x Mn x O 2-δ is undoubtedly a key class due to the flexible valence of Mn species, [19][20][21][22] and a huge size gap between Ce and Mn ions. [22,23] In principle, divalent Mn 2 + dopants with a lower positive valence would produce more charge compensating vacancies, which favor the diffusion of active oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that the catalytic activity of single CeO 2 is quite limited [1,10] . Doping transition metals into CeO 2 is a promising way to create oxygen vacancy and lattice distortion, thus leading to enhanced catalytic performance [11–18] . Among various doped CeO 2 catalysts, Ce 1‐x Mn x O 2‐δ is undoubtedly a key class due to the flexible valence of Mn species, [19–22] and a huge size gap between Ce and Mn ions [22,23] .…”
Section: Introductionmentioning
confidence: 99%